A targeted illumination optical fiber probe for high resolution fluorescence imaging and optical switching - Shinde, Anant (2017)
An optical imaging probe with targeted multispectral and spatiotemporal illumination features has applications in many diagnostic biomedical studies. However, these systems are mostly adapted in conventional microscopes, limiting their use for in vitro applications. We present a variable resolution imaging probe using a digital micromirror device (DMD) with an achievable maximum lateral resolution of 2.7 μm and an axial resolution of 5.5 μm, along with precise shape selective targeted illumination ability. We have demonstrated switching of different wavelengths to image multiple regions in the field of view. Moreover, the targeted illumination feature allows enhanced image contrast by time averaged imaging of selected regions with different optical exposure. The region specific multidirectional scanning feature of this probe has facilitated high speed targeted confocal imaging.